Workplace Neurosurveillance: Is the Employee’s Mental Privacy Protected Under International Law? (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
This paper analyses the implications for international human rights and labour law resulting from the use of neurotechnology in the workplace. It distinguishes between brain-reading devices, which collect and process neural data and may affect privacy and freedom of thought, and brain-altering technologies, which may affect mental integrity. By mapping the international, regional, and ILO frameworks, this paper highlights protection gaps created by fragmented regulation of this disruptive technology. It argues that the precautionary principle, soft-law instruments, and anticipatory regulation are essential to address these challenges. Ultimately, it contends that safeguarding dignity in the digital workplace requires a principled and proactive governance model to prevent cognitive surveillance and exploitation.
Keywords: neurotechnology; workplace surveillance; mental privacy; freedom of thought; international labour law